2022
DOI: 10.3389/fmedt.2022.969203
|View full text |Cite
|
Sign up to set email alerts
|

High—throughput and automated screening for COVID-19

Abstract: The COVID-19 pandemic has become a global challenge for the healthcare systems of many countries with 6 million people having lost their lives and 530 million more having tested positive for the virus. Robust testing and a comprehensive track and trace process for positive patients are essential for effective pandemic control, leading to high demand for diagnostic testing. In order to comply with demand and increase testing capacity worldwide, automated workflows have come into prominence as they enable highth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…59 The COVID-19 pandemic has also increased the implementation and popularity of automated high-throughput reverse transcriptasepolymerase chain reaction (RT-qPCR) for COVID-19 testing, which may benefit the development of molecular testing and precision cancer treatment. 60 Moreover, due to the effectiveness of ensuring biosafety and limiting infection, COVID-19 testing has become a landmark in patient care, with its relatively rapid turnaround and reliability.…”
Section: Reduc Ti On S In the Volume Of C Y Topathology S Pecimen S W...mentioning
confidence: 99%
“…59 The COVID-19 pandemic has also increased the implementation and popularity of automated high-throughput reverse transcriptasepolymerase chain reaction (RT-qPCR) for COVID-19 testing, which may benefit the development of molecular testing and precision cancer treatment. 60 Moreover, due to the effectiveness of ensuring biosafety and limiting infection, COVID-19 testing has become a landmark in patient care, with its relatively rapid turnaround and reliability.…”
Section: Reduc Ti On S In the Volume Of C Y Topathology S Pecimen S W...mentioning
confidence: 99%
“…However, their long production cycles and high costs make them less ideal for POC diagnostics 27 31 . Recent developments in sample-to-answer systems for COVID-19 diagnosis include rapid testing, high-throughput methods, and automated detection 32 34 . However, these systems have not become commonplace due to their cost, size, or design deficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…But some of the mutations acquired during the evolution of the viral genome may lead to failure in RT-PCR amplification, for instance the 69-70 del in the S gene [ 9 , 10 ] as well as mutations occurring in the N gene [ 11 , 12 ]. Globally, this technique is considered the gold standard for the diagnosis of COVID-19 due to its sensitivity; therefore, many industries had developed commercial kits to reduce the typical run time and improve the methodology protocol [ 13 , 14 , 15 ]. The importance of a solid and proven stability of genomic regions is pivotal to design targets for a diagnostic kit, therefore in this study we compared 48 samples identified during the daily diagnostic workflow presenting a PCR peculiar result.…”
Section: Introductionmentioning
confidence: 99%